2013
DOI: 10.5007/1980-0037.2013v15n5p517
|View full text |Cite
|
Sign up to set email alerts
|

Educação física escolar, atividade desportiva e atividade física total em adolescentes

Abstract: Less than half of adolescents reach the recommended 300 minutes per week of physical activity (PA). Physical education classes and sports participation provide opportunities for adolescents to accumulate more time for PA practice; however, little is known about the influence of these variables on the level of total physical activity of adolescents. The aim of this study was to investigate the association between the practice of physical education (PE) in schools and sports activities (SA) with the practice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
6
Order By: Relevance
“…This finding was somehow unexpected, as results of cross-sectional studies have shown positive relationship among variables 27,28 , and longitudinal and intervention studies have shown that participation in physical education classes can positively influence physical activity 29 .…”
Section: Continuesmentioning
confidence: 61%
“…This finding was somehow unexpected, as results of cross-sectional studies have shown positive relationship among variables 27,28 , and longitudinal and intervention studies have shown that participation in physical education classes can positively influence physical activity 29 .…”
Section: Continuesmentioning
confidence: 61%
“…Além deste, os resultados referentes às frequências de adolescentes insuficientemente ativos e com tempo de tela superior a três horas diárias devem ser destacados devido a sua elevada prevalência. Embora a proporção de adolescentes insuficientemente ativos tenha sido elevada, resultados de estudos brasileiros utilizando a mesma forma de medida e classificação da AF apresentaram prevalências ainda mais altas 13,17 . Outras investigações com amostras populacionais que utilizaram outros instrumentos de medida e como critério para a classificação alcançar no mínimo 300 minutos por semana de AF de intensidade moderada a vigora, também encontraram prevalências elevadas de adolescentes insuficientemente ativos, variando entre 49,8% e 80,3% ,9,14,19,26 .…”
Section: Resultsunclassified
“…Nesta perspectiva, alguns estudos vêm sendo conduzidos associando indicadores socioeconômicos com a AF e o comportamento sedentário da população jovem. Os resultados encontrados são conflitantes [13][14][15][16][17][18] , não permitindo identificar claramente como estas variáveis se associam, necessitando que mais investigações com este propósito sejam conduzidas. Esta heterogeneidade nos resultados pode estar relacionada a diferenças metodológicas entre os estudos, incluindo os procedimentos de seleção das amostras e os instrumentos de medida das variáveis.…”
Section: Associação Entre Atividade Física E Tempo De Tela Com O Níveunclassified
See 1 more Smart Citation
“…Tais limitações sugerem cautela na utilização de questionários traduzidos e adaptados nessas condições. No entanto, apesar disso, o PAQ-C traduzido subsidiou a realização de alguns estudos envolvendo crianças e adolescentes brasileiros [23][24][25][26][27] .…”
Section: Introductionunclassified